Adjuvant Transgingival Therapy with Visible Light Plus Water-Filtered Infrared-A (VIS + wIRA) in Periodontal Therapy-A Randomized, Controlled, Stratified, Double-Blinded Clinical Trial - Stefanie Anna Peikert; Anil Fischer; Anne Brigitte Kruse; Ali Al-Ahmad; Johan Peter Woelber; Kirstin Vach; Andreas Braun; Petra Ratka-Krüger (MDPI AG, 2021)
The aim of this randomized, controlled, double-blinded clinical trial was to examine the additional healing effect of transgingival visible light and water-filtered infrared-A (VIS + wIRA) in the treatment of periodontitis patients compared with the standard therapy by subgingival instrumentation (SI). Therefore, forty patients with untreated periodontitis received a non-surgical periodontal treatment. Using a split-mouth study design, one quadrant of the upper jaw was randomly either exposed to VIS + wIRA four times for 20 min within two weeks in addition to SI or received only SI. Three and 6 months after intervention, clinical parameters (probing depths (PDs), clinical attachment level, bleeding on probing (BOP), furcation, tooth mobility, plaque control record, and papilla bleeding index) were re-evaluated. In the presence of PD of 4 mm and positive BOP or PD > 4 mm, SI was performed again. Moreover, the patients were asked about their discomfort using a visual analog scale from 1 to 10 for each side of the maxilla. Statistical analysis demonstrated no differences between quadrants at re-evaluation for clinical parameters (p > 0.05) after 3 and 6 months. Concerning pain perception, patients described less pain on the irradiated side (p = 0.016). In the treatment of patients with periodontitis, VIS + wIRA did not show an additional effect on the clinical outcome after 3 and 6 months. Patients described less pain on the irradiated quadrant after treatment.